San Marino : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper for San Marino reviews developments in the financial sector and provides an update of the financial sector regulation and supervision. While Sammarinese financial institutions accept foreign deposits and managed funds to a much larger extent than comparators in neighboring regions, there are no mutual funds or international bonds issued under San Marino law unlike the common practice in several international financial centers. There is considerable room to increase the flexibility and innovation needed to remain internationally competitive while maintaining the strengths and soundness of the financial system.